Analysis Of Raw Material Supply In The Mak Sulis Business In Bengkulu City - Amelya, Tifani Rika; Afriani , Sulisti; Hidayah , Nenden Restu (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
Considering the importance of raw material inventory in business operations, a company needs to manage raw materials in a controlled manner. The main raw material used is wheat flour. In the production of bread, wheat flour is the main raw material which must always be available for the smooth production process, therefore it is necessary to carry out appropriate control and planning in the supply of the raw material for this flour. Therefore, the researcher is interested in conducting research with the title "Analysis of Raw Material Inventory in the Mak Sulis Donut Business, Bengkulu City Using the Economic Order Quantity (EOQ) Method". To collect the required data, the following data collection techniques were used: interviews, observation and documentation techniques. Data from observations from analysis of raw material supplies at the Mak Sulis Donut Business in Bengkulu City were analyzed using the Economic Order Quantity (EOQ). The results of the analysis show that to meet the raw material requirements of 10,450 kg during January 2022 to December 2022, the amount of raw material purchases of wheat flour that must be made by the Mak Sulis Donut Business in Bengkulu City so that storage costs can be kept to a minimum is 320 kg. each purchase with a purchase frequency of 33 times during one period (year). The purchase of raw materials for wheat flour must be carried out by the Mak Sulis Donut Business, Bengkulu City. Reorders should be made when inventory is 369 kg in the warehouse, with a lead time of 7 days so as not to hamper the company’s production process.